Weapons Carrying Crime during the Participation in the Anti – Government Demonstrations. Comparative Study - Ibrahim Al-Mamoori, Mohammed Ismael; Mousa Al-Murshidy, Muna Abdulaali (Opción, 2019)
The Crime of the weapons carrying during the demonstrations, was stated in the weapons law number 51 for Year 2017 where to achieve this crime, its pillars must be available and which is represented by the material pillar where the criminal behavior in it and based on the Article (24/Fourth) is carrying the weapon which must be a firearm. There also must be available is the moral pillar which takes the form of the criminal intention because it is an intention- al crime. This is in addition to the availability of its own pillar which takes the form that the weapon is carried during the participation in the demonstration. Therefore this crime does only occur if the doer carries the firearm during the demonstration i.e. carrying the weapon only takes place during the time period expanding from the start of the demonstration until its end and it is not used to carry the weapon at any other time. This Crime is an offense which is punished by the law by imprisonment for a period of not more than three years and by fine of not less than one million and not more than five million Dinars and contains a severe condition where the penalty is by imprisonment if the criminal was not permitted to carry the weapon when participating in the demonstration.